Importance of conserving large and old trees to continuity of tree-related microhabitats - Kozák, Daniel; Svitok, Marek; Zemlerová, Veronika; Mikoláš, Martin; Lachat, Thibault; Larrieu, Laurent; Paillet, Yoan; Buechling, Arne; Bače, Radek; Keeton, William S; Vítková, Lucie; Begovič, Krešimir; et al. (Conservation biology, 2023)
Protecting structural features, such as tree-related microhabitats (TreMs), is a cost-effective tool crucial for biodiversity conservation applicable to large forested landscapes. Although the development of TreMs is influenced by tree diameter, species, and vitality, the relationships between tree age and TreM profile remain poorly understood. Using a tree-ring-based approach and a large data set of 8038 trees, we modeled the effects of tree age, diameter, and site characteristics on TreM richness and occurrence across some of the most intact primary temperate forests in Europe, including mixed beech and spruce forests. We observed an overall increase in TreM richness on old and large trees in both forest types. The occurrence of specific TreM groups was variably related to tree age and diameter, but some TreM groups (e.g., epiphytes) had a stronger positive relationship with tree species and elevation. Although many TreM groups were positively associated with tree age and diameter, only two TreM groups in spruce stands reacted exclusively to tree age (insect galleries and exposed sapwood) without responding to diameter. Thus, the retention of trees for conservation purposes based on tree diameter appears to be a generally feasible approach with a rather low risk of underrepresentation of TreMs. Because greater tree age and diameter positively affected TreM development, placing a greater emphasis on conserving large trees and allowing them to reach older ages, for example, through the establishment of conservation reserves, would better maintain the continuity of TreM resource and associated biodiversity. However, this approach may be difficult due to the widespread intensification of forest management and global climate change.
Keywords: Biodiversity; stromy; Insecta; gestión forestal; forest structure; indicadores de biodiversidad; Forests; bosque primario; Trees; biodiverzita; primary forests; forest management; Carpathian Mountains; habitat tree; estructura del bosque; Conservation of Natural Resources; dendrocronología; Animals; 生境树, 生物多样性指标, 喀尔巴阡山脉, 树轮年代学, 森林结构, 森林管理, 原始森林; hábitat arborícola; Cárpatos; zachování přírodních zdrojů; hmyz; zvířata; biodiversity indicators; lesy; dendrochronology